Esprit du temps et coupe synchronique : la théorie du discours social - Marc Angenot (Corela)
In the general framework of a synchronic approach of intellectual history, the author defines the basic concepts of Social Discourse Theory seen as the method of a all-encompassing analysis of whatever is being written, printed and disseminated in a given state of society. He aims at defining a number of fundamental notions such as Discursive hegemony, Topography, Inter-discursiveness and Sociogramme.